ปัจจัยที่ส่งผลต่อภาวะผู้นำการเปลี่ยนแปลงของผู้บริหารสถานศึกษา สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาชลบุรี เขต 2 - ชูพันธ์, พรสุดา; ชมภู , วิโรฒน์; อิ่มสวาสดิ์, ประยูร (Journal of Graduate School Sakon Nakhon Rajabhat University, 2020)
The purposes of the research were to examine factors affecting transformational leadership of school administrators under Chonburi Primary Educational Service Area Office 2. The sample, obtained through stratified random sampling, consisted of 297 teachers working in schools under Chonburi Primary Educational Service Area Office 2. The sample size was determined based on the table of Krejcie & Morgan. The research instruments were a set of questionnaires and interview forms. Statistics for data analysis were mean scores (), standard deviations (S.D.), Pearson’s product moment correlation, and Stepwise multiple regression analysis. The findings were as follows: The factors in terms of personality, organizational climate, and achievement motivation of school administrators under Chonburi Primary Educational Service Area Office 2 in overall and each aspect were at a high level. The transformational leadership of school administrators under Chonburi Primary Educational Service Area Office 2 in overall and each aspect was at a high level. The factors in terms of personality, organizational climate, and achievement motivation had a relationship with transformation leadership of school administrators with a statistically significance of .01 level. The factors in terms of personality, organizational climate, and achievement motivation of school administrators affected their transformational leadership with a statistical significance of .05 level. The equations of transformational leadership of school administrators under Chonburi Primary Educational Service Area Office 2, consisted of Autonomous Climate (X7), Need for Affiliation (X13), Need for Power (X14), Agreeableness (X4), Need for Achievement (X12), Closed Climate (X11), and Conscientiousness (X5), could predict school administrators’ transformational leadership at 81.40 percent. The regression equations could be written as the following equations: The regression equation of raw scores could be summarized as follows: = .451 + .235(X7) + .112(X13) + .143(X14) + .161(X4) + .096(X12) + .056(X11) + .080(X5) And the regression equation of standardized scores could be written as follows: = .323(X7) + .139(X13) + .154(X14) + .268(X4) + .096(X12) + .076(X11) + .085(X5)